Lower limb ischemic preconditioning combined with dietary nitrate supplementation does not influence time-trial performance in well-trained cyclists. Issue 7 (July 2019) - McIlvenna, Luke C.; Muggeridge, David J.; Forrest (Nee Whyte), Laura J.; Monaghan, Chris; Liddle, Luke; Burleigh, Mia C.; Sculthorpe, Nicholas; Fernandez, Bernadette O.; Feelisch, Martin; Easton, Chris
Abstract: Objectives: Dietary nitrate (NO3 − ) supplementation and ischaemic preconditioning (IPC) can independently improve exercise performance. The purpose of this study was to explore whether NO3 − supplementation, ingested prior to an IPC protocol, could synergistically enhance parameters of exercise. Design: Double-blind randomized crossover trial. Methods: Ten competitive male cyclists (age 34 ± 6 years, body mass 78.9 ± 4.9 kg, V ⋅ O 2 p e a k 55 ± 4 mL kg min −1 ) completed an incremental exercise test followed by three cycling trials comprising a square-wave submaximal component and a 16.1 km time-trial. Oxygen uptake ( V ⋅ O 2 ) and muscle oxygenation kinetics were measured throughout. The baseline (BASE) trial was conducted without any dietary intervention or IPC. In the remaining two trials, participants received 3 × 5 min bouts of lower limb bilateral IPC prior to exercise. Participants ingested NO3 − -rich gel (NIT + IPC) 90 min prior to testing in one trial and a low NO3 − placebo in the other (PLA + IPC). Plasma NO3 − and nitrite (NO2 − ) were measured immediately before and after application of IPC. Results: Plasma [NO3 − ] and [NO2 − ] were higher before and after IPC in NIT + IPC compared to BASE ( P  < 0.001) but did not differ between BASE and PLA + IPC. There were no differences in V ⋅ O 2 kinetics or muscle oxygenation parameters between trials (all P  > 0.4). Performance in the time-trial was similar between trials (BASE 1343 ± 72 s, PLA + IPC 1350 ± 75 s, NIT + IPC 1346 ± 83 s, P  = 0.98). Conclusions: Pre-exercise IPC did not improve sub-maximal exercise or performance measures, either alone or in combination with dietary NO3 − supplementation.